Risk Factors for the Comorbidity of Hypertension and Renal Cell Carcinoma in the Cardio-Oncologic Era and Treatment for Tumor-Induced Hypertension - Ba, Zhengqing; Xiao, Ying; He, Ming; Liu, Dong; Wang, Hao; Liang, Hanyang; Yuan, Jiansong (Frontiers in Cardiovascular Medicine, 2022)
Advances in tumor diagnosis and treatment, especially the use of targeted therapies, have remarkably improved the survival rate of patients with renal cell carcinoma (RCC), accompanied by higher hypertension incidence among RCC patients, reflecting the coming of a cardio-oncologic era. Therefore, for patients with RCC and hypertension simultaneously, finding risk factors for the comorbidity and giving better clinical treatment have been urgent problems. In this review, we thoroughly investigated risk factors for the comorbidity of hypertension and RCC based on preclinical and clinical studies. We then discussed measures for reducing the comorbidity and treatment for hypertension in RCC patients. We also summarized the deficiency of current studies and pointed out future directions.